On Discriminating between Geometric Strategies of Surface-Based Orientation - Sturz, Bradley R.; Bodily, Kent D. (Frontiers in Psychology, 2012)
Recently, a debate has manifested in the spatial learning literature regarding the shape parameters by which mobile organisms orient with respect to the environment. On one hand are principal-axis-based strategies which suggest that organisms extract the major and minor principal axes of space which pass through the centroid and approximate length and width of the entire space, respectively. On the other hand are medial-axis-based strategies which suggest that organisms extract a trunk-and-branch system similar to the skeleton of a shape. With competing explanations comes the necessity to devise experiments capable of producing divergent predictions. Here, we suggest that a recent experiment (i.e., Sturz and Bodily, 2011a) may be able to shed empirical light on this debate. Specifically, we suggest that a reevaluation of the design reveals that the enclosures used for training and testing appear to produce divergent predictions between these strategies. We suggest that the obtained data appear inconsistent with a medial-axis-based strategy and that the study may provide an example of the types of designs capable of discriminating between these geometric strategies of surface-based orientation. Such an approach appears critical to fundamental issues regarding the nature of space and spatial perception.